International Students’ use of Multilingual Information Access (MLIA) tools: A Survey - Nzomo, Peggy; Rubin, Victoria; Ajiferuke, Isola (Proceedings of the Annual Conference of CAIS / Actes du congrès annuel de l'ACSI, 2013)
This research presents the results of a case study on potential users of Cross Language Information Retrieval (CLIR) systems –international students at the University of Western Ontario. The study is designed to test their awareness of Multi-Lingual Information Access (MLIA) tools on the internet and in select electronic databases. The study also investigates how non-native English speakers cope with language barriers while searching for information online. Based on the findings, we advocate for designing systems that incorporate CLIR options and other MLIA tools to support users from diverse linguistic backgrounds with varying language proficiency levels. Cette recherche présente les résultats d’une étude de cas auprès d’utilisateurs potentiels, des étudiants internationaux de l’University of Western Ontario, d’un système de repérage d’information par langue croisée (RILC). L’étude est conçue pour tester leur connaissance d’outils d’accès à l’information multilingues (AIM) sur Internet et dans certaines bases de données électroniques. L’étude s’intéresse également aux moyens que prennent les locuteurs non natifs de l’anglais pour palier aux barrières linguistiques lorsqu’ils cherchent de l’information en ligne. Selon les résultats, nous recommandons de concevoir des systèmes qui incorporent des options de RILC et d’autres outils d’AIM pour aider les utilisateurs d’origine linguistique diverse ayant des niveaux de maîtrise linguistique différents.